Evaluación de un recubrimiento comestible con la adición de proteína de suero lácteo y aceite de oliva en la conservación de fresas (fragaria). - Rojas Comina, Diana Karolina (2022)
Actually, the edible coatings and films application into food industry is great interest, because it is a technology, what can extend the fruits shelf life. Strawberry is a fruit with high nutritional value, what it is very popular among consumers, into Ecuador, it is grown, harvested and consumed every year month. The aim this study is to extend the strawberries conservation time (Fragaria), through an edible coating development, it has an innovative purpose, due to the whey protein use, further, it is recommended for the coatings preparation antioxidant use for preventing future microbial load, such as, olive oil. It was analyzed the treatments physicochemical properties with protein and olive oil different concentrations in the strawberry, and thanks to the InfoStat and Excel programs were determined the best treatment for subsequent microbiological analysis. It was used an experimental design A*B+1, where factor A is the whey protein concentration (a_1:15 g y a_2:25 g) and factor B is the olive oil concentration ( b_1:5 g⁡y b_2:10 g⁡), whose were dissolved into water 500 ml, by getting eight treatments and one control for later analysis. The treatments were assessed during an eight days interval, and then, it was contrasted the physical-chemical analyses, they were got, what the treatment that preserved the properties greatest number is t2 (a_1 b_2) (whey protein 15 g and olive oil 10 grams), whose values are: 86.15% humidity percentage, a 3.99 pH; soluble solids 10.50 oBrix, titratable acidity with a 0.06% percentage, a 4.39% weight loss and firmness 6.54 N. At the end, the microbiological analyzes were examined into a certified laboratory, the assessed parameters are: total coliforms, escherichia coli and aerobic mesophiles, for verifying, what the got results are found within the set range, into comparison with authors, such as Cabrera 2013 and Center for Food Safety, 2014. With the described analyzes, above, it is shown, which the edible coating by adding whey protein and olive oil, if it influences the strawberries conservation.